(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper describes the consumption trends of pesticides over the period of 2003 to 2017 across the states in India. The industrialization of the agricultural sector has increased the chemical burden on natural ecosystems. Pesticides are chemicals used in agricultural lands, public health programs, and urban green areas in order to protect plants and humans from various diseases. The pesticide economy of India is more export-oriented in nature. The growth rate of domestic consumption of pesticides over the years has shown wide fluctuations, though the overall trend is negative. Analyzing the trend of pesticide consumption in 28 states and Union Territories (UTs) of India for the period 2003 to 2017, a positive growth trend has been observed in 17 states/UTs. The highest growth has been observed in Jammu & Kashmir, Andaman & Nicobar Islands and Tripura. Uttar Pradesh, Maharashtra, Andhra Pradesh, Punjab and Haryana are the states that accounted for 70 per cent of total pesticide consumption. The use-intensity of pesticides has been found highest in Jammu and Kashmir, followed by Punjab and Haryana. However, Punjab and Haryana have exhibited a declining trend in pesticide consumption. On the contrary, Meghalaya where the intensity of application is comparatively low, has registered an increasing trend in pesticide consumption. In the areas of North East Region in general apply low levels of pesticides and are in a declining mode of consumption, except the states like Sikkim, Meghalaya, Tripura, Manipur and Nagaland where noted positive growth rate. This paper has also highlighted the critical review of government policy.